2009
DOI: 10.1021/jo8024797
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Scalable Ritter Reaction for the Synthesis of tert-Butyl Amides

Abstract: A scalable procedure for the conversion of nitriles to N-tert-butyl amides via the Ritter reaction was optimized employing tert-butyl acetate and acetic acid. The reaction has a broad scope for aromatic, alkyl, and alpha,beta-unsaturated nitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…The former corresponds to the commonly occurring cyanoethyl-RNA adducts (plus 54 amu) [25] whereas the latter likely refers to tert-butyl RNA adducts (plus 56 amu). To support this hypothesis, we changed the solvent of the detritylation solution from dichloroethane to acetonitrile, which we expected to act as carbocation scavenger, [40] and, indeed, the plus 56 amu byproduct either diminished below the detection limit, or decreased significantly (see the Supporting Information, Figure S1). …”
Section: Resultsmentioning
confidence: 99%
“…The former corresponds to the commonly occurring cyanoethyl-RNA adducts (plus 54 amu) [25] whereas the latter likely refers to tert-butyl RNA adducts (plus 56 amu). To support this hypothesis, we changed the solvent of the detritylation solution from dichloroethane to acetonitrile, which we expected to act as carbocation scavenger, [40] and, indeed, the plus 56 amu byproduct either diminished below the detection limit, or decreased significantly (see the Supporting Information, Figure S1). …”
Section: Resultsmentioning
confidence: 99%
“…14 Therefore, examples such as triphenylmethyl formate 62 or tert-butyl acetate 63 can be employed in place of the corresponding alcohols or alkenes to obtain the controllable reaction conditions necessary for large-scale preparations. 64 The reactions can be conducted as a flow system by using microfluidic devices to control the various reaction parameters, 65 and the exothermic nature of the reaction can also be mitigated by (1) adding the components in small quantities over time and (2) …”
Section: Chmentioning
confidence: 99%
“…The one exception was acetonitrile, which underwent conventional acyclic amide formaOxazine products are also obtained by reactions of β-chloroketones under Lewis acid conditions (equation64), and from the direct reaction of malonyl chloride derivatives with nitriles (equation 65) 139,140. Oxetanes 106 can also afford dihydro-1,3-oxazines in excellent yield (equation 66) 141.…”
mentioning
confidence: 99%
“…Reddy reported that aromatic and aliphatic nitriles react with tert-butyl acetates in the presence of sulfuric acid to give the corresponding N-tert-butyl amides in excellent yields [3]. The same reaction can also be catalyzed by acetic acid and H 2 SO 4 [4].…”
Section: Introductionmentioning
confidence: 99%